CONCEPT ANALYSIS OF THE FIELD OF SCIENCE AND THE STUDY OF BASIC EDUCATION - Restu Fauziah; Firman; Riska Ahmad (Literasi Nusantara, 2021)
Education is an important part in a country where education plays a big role as a forum for creating intelligent and noble sons and daughters of the nation. Therefore, education is very important to educate the nation's children. It is understood that an educator must have the ability, understanding, knowledge of education, knowledge is the main object of education. Education as a science, namely educational theory, reflection on education, in the broad sense of education, namely science that studies questions that arise in educational practice. Education is an effort to equip students in the form of knowledge, knowledge and skills that are useful for themselves, the community and the surrounding environment. Basically, Education is closely related to science because the main object of education is science. Education is an activity of transferring knowledge from educators to students. A process of transferring knowledge which is generally carried out in three ways, namely verbal, written and deed. Education is a fundamental or fundamental phenomenon in human life, after all there is education.